Segurança alimentar e nutricional : um referencial político no combate à pobreza - Xavier, Jair dos Santos (2020)
The research developed here is the result of a greater interest in analyzing sociologically or the phenomenon of public policy implementation. So propose not to fit into a pragmatic and functional perspective, evaluate the functioning and apply a public political policy. This is the truth, a research in the area of Political Sociology, dedicated to understanding how the Brazilian State is configured and its relations with Society. From this perspective, the whole discussion around Food and Nutritional Security, presents itself as a discussion that permeates actions to combat poverty and social inequalities. This concern is amplified with the latest indicators of an increase in the condition of population poverty and a gradual return to hunger in Brazil, indicators that have already been overcome, in other political scenarios. The public policy of Food and Nutrition Security - SAN in the municipality of Aracaju - SE, shows as the object and field of all research, with no sense of its idealization and execution, as a state resource, capable of promoting actions, around a public cause combating hunger and food security. In order to apprehend this set of relationships, this work makes use of a qualitative methodology of relational business, going through a document analysis, observation and interviews, with members, both from civil society; management, academic and professional advisers in the field; how much of the State; following the work of the Municipal Social Assistance Secretariat of the city of Aracaju - SE. No intention to apprehend how relations produce the repertoires of interaction between the State and civil society, from the perspective of training the ideological and political references of its actors. In addition, this discussion in the SAN allows us to understand hunger and the situations of food security that are socially constructed. As said by Josué de Castro (1984), "Hunger is not a natural phenomenon, it is a social phenomenon, the product of defective economic structures".